SPATIAL AND TEMPORALVARIATION OF DISSOLVED INORGANIC NUTRIENTS, AND CHLOROPHYLL-α IN A TROPICAL ESTUARY IN NORTHEASTERN BRAZIL: DYNAMICS OF NUTRIENT REMOVAL (Brazilian Journal of Oceanography, 2015)
Monthly sampling campaigns were carried out between February 2010 and January 2011 to evaluate the spatial and temporal distribution of nutrients (ammonium, nitrite, nitrate, dissolved organic nitrogen, phosphate, dissolved organic phosphorus and silicate) and chlorophyll-α along a salinity gradient in the tropical Cachoeira River estuary, subject to the untreated effluents of a sewage treatment plant (STP). During the study period the lowest and highest river discharge occurred in February and April 2010, respectively. High river outflow promoted increased concentrations of inorganic nitrogen and silicate but did not affect the concentration of phosphate. Based on the chlorophyll-α concentration the estuary may be classified as eutrophic / hypereutrophic in its inner portion and mesotrophic in the lower region. The inner portion is more affected by the nutrient load carried out by the river and STP, while dilution by seawater contributed to the reduction of the nutrient concentrations in the lower reaches of the estuary. The results indicate that nutrient uptake by the phytoplankton is the most effective dissolved inorganic nutrient removal processes, especially for phosphate. Mixing diagrams suggest that the coupling of nitrification and denitrification processes is also responsible for the elimination of nitrogen from this ecosystem.